THE IMPORTANCE OF OBEDIENCE & FREE WILL IN JOHN MILTON’S PARADISE LOST - Ismail Radam, Halima (International Journal of Psychosocial Rehabilitation, 2020)
One can argue that the notion of free will is the unconditional supremacy given to humans by God to create their own faith and destiny. However, Milton expressed his own perspective of free will as a singular authorization of obedience for him and for others to God. The main intention of this study is to highlight the question of obedience and free will in John Milton's poem Paradise Lost (1667). This study will offer an answer to the key question on “what is the Miltonic obedience?” This study will examine not only the outlined unadventurous literary texts set by Milton but rather focus on the concept of obedience and free will in John Milton’s Paradise Lost (1667). Furthermore, this study will highlight the Miltonic theory of obedience and free will as an attempt to understand and to recreate his ideologies of free will and God’s will of obedience from Milton’s perspective. This study will be textually limited to John Milton’s Paradise Lost (1667). Theoretically, this study will follow the method of theological and philosophical literary interpretation to fully comprehend Milton’s conception of obedience and free will. This study will undertake the classic literary and the religious Christian methodology for further analytic understanding in highlighting both Milton’s philosophical classicism and Milton’s theoretical Christianity.